Chronic caffeine ingestion improves memory and learning and increases neuronal population and dendritic length in the hippocampus of adult mice (Nigerian Journal of Physiological Sciences, 2021)
Caffeine is the most widely consumed psychoactive drug in the world, ingested as natural components of chocolate, coffee and tea and as added components to soda and energy drinks. Here we assessed behavioural changes caused by chronic caffeine administration as well as morphological changes within specific regions of the adult mice brain: the hippocampus and amygdala. Twenty-four adult male albino mice were randomly divided into three groups. Caffeine was administered daily by gavage for 8 weeks at a dosage of 20 mg/kg for low dose (LD) group and 60 mg/kg for high dose (HD) group while the third group served as control (CNT). After the period of administration, neurobehavioural tasks were carried out; Morris water maze for learning and memory open field test and elevated plus maze test for anxiety. The mice were sacrificed; their brain tissues were harvested and processed for H&E, Cresyl violet and Golgi staining, and assessed qualitatively and quantitatively. Quantitative data from the neurobehavioural tests and neuronal cell counts were expressed as means ± standard errors of means and compared across the groups using analysis of variance (ANOVA). Significance was set at p< 0.05.Mice in the high dose group learnt faster and had significantly increased number of platform crossings in the Morris water maze test. There was, however, a slightly increased level of anxiety in the caffeine-treated mice, compared to controls. Histo-morphometric analysis revealed significantly increased number of pyramidal neurons in the hippocampus in the low dose group, but a decreased neuronal count in the amydala of the low dose and high dose groups compared to controls. The pyramidal neurons in the hippocampus of the caffeine-treated mice had increased apical dendritic length compared to the controls. Our findings strengthen the available data suggesting that prolonged caffeine intake improves cognition, and this process could be mediated by promoting the growth of dendrites and increased number of neurons. However, this is coupled with an increased tendency to be anxiogenic.